Facing terror - McDonnall, Carrie (Nashville : Integrity Publishers, 2005)
"The true story of how an American couple paid the ultimate price because of their love of Muslim people"--Provided by publisher.
Keywords: McDonnall, David, -- d. 2004.; McDonnall, Carrie; Missionaries -- Biography; Missions to Muslims; Missions -- Iraq; Missions -- Middle East